Socio-economic marginalization and plasma HIV-1 RNA non-detectability among individuals who use illicit drugs in a Canadian setting - RICHARDSON, Lindsey A. (AIDS, 2015)
OBJECTIVE: Given that people who use illicit drugs (PWUD) often engage in prohibited income generation to support their basic needs, we sought to examine the role of these activities in shaping antiretroviral therapy (ART) adherence and plasma HIV RNA-1 viral load suppression among HIV-infected PWUD. DESIGN: Longitudinal analyses among HIV-positive, ART exposed PWUD in the AIDS Care Cohort to evaluate Exposure to Survival Services prospective cohort study (2005–2013). METHODS: Generalized linear mixed effects and mediation analyses examined the relationship between prohibited income generation (e.g. sex work, drug dealing, theft, street-based income) and virologic suppression (plasma viral load ≤ 50 copies/mL plasma) adjusting for adherence and potential confounders. RESULTS: Among 687 HIV-infected PWUD, 391 (56.9%) individuals reported prohibited income generation activity during the study period. In multivariate analyses, prohibited income generation remained independently and negatively associated with virologic suppression (adjusted odds ratio: 0.68, 95% confidence interval: 0.52–0.88) following adjustment for hypothesized confounders, including high-intensity drug use, ART adherence and homelessness. While partially mediated by ART adherence, the relationship between prohibited income generation and virologic suppression was maintained in mediation analyses (Sobel statistic = −1.95, p=0.05). CONCLUSIONS: Involvement in prohibited income generation decreases the likelihood of virologic suppression directly and indirectly through its negative association with ART adherence. These findings suggest that linkages between socio-economic marginalization, the criminalization of illicit drug use and insufficient employment opportunities may produce barriers to access and retention in care. Programmatic and policy interventions that decrease socio-economic vulnerability may therefore reduce HIV-related morbidity, mortality and onward transmission.